Cinta Erich Fromm Kepada Rabi’ah Al-Adawiyah - muhammad walidin iskandar (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2017)
Problems is love can be included to psychology domain remember he go together is psychological someone. Hand in glove of its bearing with this research, hence in research of art there are a space to analyse belleslettres with approach is art psychology. This research use approach is art psychology and theory weared was Eric Fromm psychology theory, especially its theory about love. According to Fromm, form relegius from love of[is so-called with God love psychologically is not differ. One definitive matter is that essence love to that God on a par with essence love to human being. Love is human and the relationship in line with growth love human being to God. Love to God started from a period to human being not yet recognized something and still depend on strength or element outside him. Then human being recognize God love which is matriarkhal so-called with Davit. Principal of this matriarkhal love is equality. Key word: Love, Approach Psyicology Psycology Eric Fromm of Theory